A magnetic composite filler and preparation method thereof

By designing magnetic composite filler, using the combination structure of hollow outer shell and hollow porous balls, the porosity is increased and the flow-through hole design is solved, and the existing biological filler has poor adhesion and blockage in waste gas treatment is achieved, achieving more efficient waste gas degradation Effect.

CN115672013BActive Publication Date: 2025-02-11ZHEJIANG OCEAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211208950.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-02-11
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

In the waste gas treatment, existing biological fillers have problems such as poor microorganism adhesion, small porosity, easy blockage and excessive pressure loss, resulting in poor waste gas treatment effect.

Method used

A magnetic composite filler is designed to combine with hollow porous spheres through the hollow outer shell to increase the internal porosity, and to design the gas evenly disperse through the flow holes to extend its residence time. At the same time, the outer shell and porous spheres are magnetic, enhancing the growth and degradation ability of microorganisms.

Benefits of technology

It effectively avoids filler blockage, reduces gas mass transfer resistance, improves microorganism adhesion and degradation efficiency, and significantly improves the treatment effect of exhaust gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115672013B_ABST
    Figure CN115672013B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of waste gas treatment technology, and specifically to a magnetic composite filler and a preparation method thereof, which can be used as a biological filler in biochemical devices. The present invention is a combination of a hollow spherical outer shell and a built-in porous ball, which has the characteristics of high porosity, high specific surface area and high airflow permeability, ensuring that the airflow is fully in contact with the filler, and taking into account the smooth flow of gas channels, reducing the pressure loss in the system. At the same time, the filler is conducive to the uniform dispersion of gas in the reactor, improves the space utilization rate, increases its contact area with microorganisms on the surface of the porous filler, and strengthens the degradation effect. In addition, by magnetizing the outer shell and the porous ball, a high-density stable heteropolar magnetic field is formed, the magnetic effect of microorganisms is stimulated, the activity of metabolic enzymes is increased, the biodegradation process of organic matter is strengthened, and the purification effect of organic matter in waste gas is improved. The present invention has a wide source of raw materials, good economy and high efficiency and energy saving, and can be extended to various types of waste gas purification processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste gas treatment, and in particular to a magnetic composite filler and a preparation method thereof. Background Art

[0002] At present, waste gas is mostly treated by chemical treatment or biodegradation. Among them, biotechnology is a green and clean treatment method, which degrades waste gas substances into harmless substances such as carbon dioxide and water. Since biotechnology does not produce toxic and harmful byproducts during use and is environmentally friendly, the application of biotechnology has gradually been favored by society and families. As we all know, biological fillers are one of the core technologies of biodegradation of waste gas. They provide more space for microorganisms to grow; at the same time, the degradation performance of microorganisms is also closely related to the material, structure, and physical and chemical properties of the fillers in the reactor.

[0003] There are many different types of biological fillers, mainly fixed fillers, hanging fillers, suspended fillers and combined fillers. The larger the contact area between the filler and the microorganism, the more corresponding attached microorganisms will be, and the conversion rate of the corresponding difficult-to-degrade substances will be greatly improved. Traditional biological fillers are generally made of a mixture of polypropylene plastics, filler foams and other polymers; but in actual application, the surface of the modified filler will gradually be smoothed under the continuous water flow, the wettability of the surface will decrease, and the corresponding hydrophilicity will deteriorate. Due to the poor hydrophilicity and biological affinity of the biological filler, the contact angle of the biological filler surface is high, and the microbial adhesion is poor, which also leads to its deficiencies in the biofilm speed, biofilm amount and the tightness between the film and the filler, further affecting the waste gas treatment efficiency. Most of the existing biological fillers are modified by improving the hydrophilic affinity of their surface, but when the hydrophilicity of the modified filler is better, the thickness of the liquid film on its surface increases significantly, and the corresponding gas mass transfer resistance also increases, resulting in poor overall degradation performance. In general, the thickness of the liquid film on the surface of the packing must be strictly controlled so that it is in a suitable area to ensure normal mass transfer between gas and liquid.

[0004] In addition, with the development of waste gas biodegradation technology, more and more researchers have begun to study magnetic treatment technology and apply it to the field of waste gas degradation. The traditional setting of a magnetic field outside the waste gas biodegradation reactor can greatly increase the biodegradation rate; but due to the huge space occupied by industrial waste gas treatment facilities, the cost of setting up an external magnetic field is high, which is not conducive to industrial production. On the other hand, since the current is prone to heat during the magnetization process, there are certain safety hazards in the external magnetic field. All these factors have greatly restricted its industrial development; the built-in magnetic field can well avoid such problems, with low production and maintenance costs, and can enhance the biodegradation of waste gas. Summary of the invention

[0005] The present invention aims to overcome the problems in the prior art of poor microbial adhesion, small porosity, easy clogging of fillers, and excessive pressure loss resulting in poor waste gas treatment effect, and provides a magnetic composite filler and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0007] A magnetic composite filler comprises an outer shell, a cavity is arranged inside the outer shell, a flow hole connected to the cavity is also arranged on the outer shell, a porous ball is arranged in the cavity, porous filler is filled between the porous ball and the inner wall of the outer shell, and the porous ball and the outer shell are magnetic.

[0008] Most traditional biofiller structures use a hollow sphere composed of a semicircular auxiliary sheet and a central axis. The filler is made of polyethylene mixed with a small amount of polypropylene by injection molding. It has a simple structure, low cost, large specific surface area, and is easy to form biofilms. However, when this type of biofiller degrades waste gas, the spheres collide with each other, and the various auxiliary sheets mesh and rub against each other, causing the biofilm to fall off very easily. Existing biofillers generally use a mesh cage shape composed of two mesh-shaped hemispheres buckled into a mesh sphere. The material is polyethylene mixed with a small amount of polypropylene and other filling powders by injection molding. This configuration is conducive to the growth of microorganisms and biofilms and can promote the degradation of organic matter by microorganisms. Because the biofilm in this type of biofiller is not easy to renew and fall off, the microorganisms in the filler grow excessively and easily clog the filler, resulting in poor mass transfer performance inside and outside the mesh cage-shaped biofiller and between biofilms.

[0009] The present invention designs a magnetic composite filler. It includes an outer shell, a cavity is arranged inside the outer shell, a flow hole connected to the cavity is also arranged on the outer shell, a porous ball is arranged in the cavity, and a porous filler is filled between the porous ball and the inner wall of the outer shell. The filler is combined with the hollow outer shell and the porous ball with a hollow structure, and the internal porosity is significantly increased, which effectively avoids the clogging of the filler. The design of the flow hole is conducive to uniformly dispersing the flow direction of the gas in the system and prolonging its residence time; it also reduces the resistance encountered by the gas during the circulation process, and the pressure loss in the system is also greatly reduced. In addition, the outer shell and the porous ball are magnetized so that they have constant weak magnetism, which is beneficial to the growth and reproduction of microorganisms. At the same time, the existence of the heteropolar magnetic field enhances the activity of the enzyme in the degradation bacteria to a certain extent, so that the waste gas degradation rate is accelerated. In addition, filling the porous filler between the porous ball and the inner wall of the outer shell helps to promote the microorganism to adhere to the porous filler; this also increases the contact area of ​​the microorganism on the porous filler, and promotes more microorganisms to have a magnetic effect. By adopting an outer shell filled with a static magnetic field in all directions and assembling and matching porous balls with porous fillers, a magnetic composite filler with stable performance is formed, thereby effectively improving its degradation effect on exhaust gas.

[0010] Preferably, the outer shell comprises two upper and lower half shells, and the half shells are interlocked with each other to form a complete spherical outer shell.

[0011] As further preferred, the outer shell can be a polyhedral sphere, or a hollow sphere, or a solid sphere structure, and the outer shell has a large surface area.

[0012] The structure of a complete spherical outer shell is formed by inserting the upper and lower half shells into each other, so that the gas in the system is blocked by the spherical surface when passing through the outer shell, which also causes the gas flow to bend and tilt to a certain extent, thereby reducing the intake rate of the exhaust gas. At the same time, the movement path of the airflow is extended, which causes the gas to gradually increase its residence time in the system. These changing factors promote the full contact between microorganisms and exhaust gas to a certain extent, and it also further improves the degradation performance of microorganisms on exhaust gas.

[0013] Preferably, the outer shell is provided with radially staggered flow sheets, and flow holes communicating with the cavity are formed between adjacent flow sheets.

[0014] The arrangement of multiple circulation sheets effectively increases the specific surface area of ​​the magnetic composite filler, which is conducive to the growth of microorganisms. The design of the circulation holes is conducive to the uniform dispersion of the gas in the system and prolonging its residence time. The resistance encountered by the gas during the circulation process is reduced, and the pressure loss in the system is also greatly reduced.

[0015] Preferably, two connecting rods for fixing to the outer shell are symmetrically arranged on the outer surface of the porous ball, so that the porous ball can be suspended inside the cavity through the connecting rods.

[0016] As a further preferred embodiment, the porous ball has a hollow structure inside, and the porous ball is formed by two left and right porous hemispheres interlocked with each other, with a certain gap between the left and right porous hemispheres.

[0017] The porous ball is suspended inside the cavity by a connecting rod, and its internal porosity exceeds 90%, which can effectively avoid filler clogging. At the same time, during the degradation process, the porous filler is fixedly filled between the porous ball and the inner wall of the shell, and less than 50% of the space is occupied by microorganisms. The presence of the porous ball with a hollow structure inside further promotes that the pressure loss in the system is always small.

[0018] Preferably, the porous filler has a pore size of 0.5 to 2 mm and a porosity greater than 90%.

[0019] As further preferred, the porous filler is a combination of one or more of burr balls, polyurethane foam, and polyurethane sponge.

[0020] The porosity of the porous filler is greater than 90%, which is conducive to enhancing the adhesion of microorganisms on the surface of the porous filler. At the same time, the pore size of the porous filler is selected to be 0.5 to 2 mm, which plays a role in drainage and dispersion of the gas in the system. When the pore size is less than 0.5 mm, the porous filler is approximately a solid structure. It is difficult for the gas to pass through when it flows in, and the resistance encountered is too large, and the corresponding pressure loss will increase. When the pore size is greater than 2 mm, the gas flows directly through when it flows in; although it is not subject to resistance, it has no drainage and dispersion effect, which also indirectly shortens the residence time of the gas in the system, further affecting the waste gas degradation rate. In addition, the porous filler is fixedly filled between the porous ball and the inner wall of the shell, which is conducive to the renewal and shedding of the biofilm on the surface of the porous filler.

[0021] Preferably, the outer shell and the porous ball include the following components, calculated by weight: 60-90 parts of plastic, 2-5 parts of activated carbon, 5-15 parts of magnetic powder, 0.5-4 parts of liquid dispersant, 0.5-3 parts of silane coupling agent, 1-3 parts of starch, 1.5-4 parts of diatomaceous earth, 1-5 parts of hydroxyapatite, and 1-5 parts of polyvinyl alcohol.

[0022] As further preferred, the magnetic powder is a combination of one or more of barium ferrite magnetic powder, cobalt ferrite magnetic powder, and iron oxide magnetic powder.

[0023] There are a small amount of metal elements in the enzymes in the degradation bacteria, all of which have certain paramagnetic properties. Under the action of the heteropolar magnetic field, they will rearrange and move along the direction of the magnetic field. These influencing factors increase the activity of the enzyme. Since the enzyme activity helps to promote the metabolism in the microorganism, this also gradually increases the rate of waste gas degradation. In addition, since the degradation bacteria themselves have certain magnetism, under the action of the heteropolar magnetic field, the degradation bacteria are more easily adsorbed on the surface of the magnetic composite filler, which also increases the number of microorganisms on the surface of the magnetic composite filler, and ultimately improves the overall degradation performance of the waste gas.

[0024] On the other hand, under a constant weak magnetic field environment, the concentration of dissolved oxygen in water will show an increasing trend. Oxygen, as a paramagnetic substance, produces active oxygen with high oxidizing properties, which accelerates the oxidation of organic pollutants in water to a certain extent; the corresponding enzyme activity shows a trend of gradual increase, which eventually leads to a decrease in the concentration of organic pollutants in water. At the same time, during aeration, oxygen will be adsorbed near the magnetic composite filler under the action of the magnetic field, which will also increase the oxygen concentration on the surface of the magnetic composite filler, further promoting the reproduction of aerobic microorganisms.

[0025] Each filler to which magnetic powder is added is equivalent to a miniature biological contact oxidation reactor with a magnetic field, which enables oxygen and microorganisms to attach to the surface of the magnetic composite filler more quickly; this can also effectively shorten the biofilm formation time and improve the waste gas degradation effect.

[0026] Activated carbon, starch, diatomaceous earth, hydroxyapatite and polyvinyl alcohol can all provide good nutrition and growth environment for the growth and reproduction of microorganisms. They can increase the number of microorganisms attached to the surface of magnetic composite fillers to a certain extent, thereby improving the biological activity of microorganisms and ultimately accelerating the biodegradation rate of waste gas.

[0027] Starch is a polyglucose that can provide sufficient nutrients for microorganisms. The addition of starch enhances the affinity between the magnetic composite filler and microorganisms, and can also be used as a pore-forming agent. When the magnetic composite filler degrades waste gas, the starch dissolves in water or is consumed by microorganisms, resulting in a large number of gaps on the surface of the magnetic composite filler, which also increases the specific surface area of ​​the magnetic composite filler and the corresponding porosity, which increases the number of microorganisms attached to the filler surface. The micropores formed by starch are conducive to the growth and reproduction of microorganisms. When it reaches a certain level, it also further adjusts the density of the magnetic composite filler.

[0028] Activated carbon has excellent adsorption properties. When the weight of activated carbon is less than 2 parts, the amount of biofilm increases significantly with the increase of activated carbon addition. When the weight of activated carbon exceeds 5 parts, it has basically no effect. Diatomaceous earth has excellent properties such as large specific surface area, high porosity, large adsorption capacity and good adsorption due to its unique multi-level pore structure. It is beneficial to improve the microbial adhesion on the surface of magnetic composite fillers; at the same time, because it contains a small amount of organic matter, it can also provide certain nutrients for microorganisms. Hydroxyapatite can participate in metabolism in organisms and has good biological activity. It can provide nutrients for microorganisms. Polyvinyl alcohol has good film-forming properties and good hydrophilicity, which is conducive to biodegradation.

[0029] Preferably, the liquid dispersant is white mineral oil, vegetable oil or a combination of both.

[0030] Adding white mineral oil and vegetable oil liquid dispersants to the plastic particles, fully mixing and stirring, is conducive to the liquid dispersant sticking to the surface of the plastic particles more evenly, making it difficult to fall off and evenly dispersed. The introduction of dispersants helps to increase the roughness of the plastic particle surface and improve the adhesion of microorganisms. In addition, white mineral oil and vegetable oil liquids also play a good lubricating role in the subsequent plastic granulation process.

[0031] Preferably, the plastic is a combination of one or more of polyethylene, polypropylene, and acrylonitrile-butadiene-styrene copolymer.

[0032] Plastics should be thermoplastic resin materials, which are non-toxic to microorganisms, have good biological adaptability, and are beneficial to the growth and reproduction of microorganisms. Thermoplastic resin materials have good plasticity, good thermal stability and are easy to process and shape; they also have good chemical stability and strong acid and alkali corrosion resistance; their corresponding impact resistance is excellent, which is also beneficial to prevent filler aging and extend service life.

[0033] A method for preparing a magnetic composite filler comprises the following steps:

[0034] (S.1) crushing, sieving and classifying plastic, activated carbon, silane coupling agent, starch, diatomaceous earth, hydroxyapatite and polyvinyl alcohol, heating and drying, and naturally cooling to room temperature to obtain a solid mixed raw material;

[0035] (S.2) fully mixing the solid mixed raw material and the liquid dispersant in step (S.1), adding magnetic powder, stirring evenly and granulating to obtain a mixed filler;

[0036] (S.3) injection molding the mixed filler in step (S.2), and then magnetizing to obtain the outer shell and the porous ball;

[0037] (S.4) Assembling and fixing the outer shell and porous balls obtained in step (S.3) with the porous filler to obtain a magnetic composite filler.

[0038] The specific preparation method of the present invention is:

[0039] (S.1) 60 to 90 parts of plastic, 2 to 5 parts of activated carbon, 0.5 to 3 parts of silane coupling agent, 1 to 3 parts of starch, 1.5 to 4 parts of diatomaceous earth, 1 to 5 parts of hydroxyapatite, and 1 to 5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200 to 500 mesh sieve and classified, and then heated and dried at 50 to 90° C. for 5 to 48 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0040] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 0.5 to 4 parts of liquid dispersant until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 5 to 15 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0041] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, performing injection molding at 140-180° C. to obtain the outer shell and the porous ball, and then placing them into a magnetizer of 8000-20000 GS for magnetization, so that the outer shell and the porous ball have a constant magnetic field of 20-100 GS;

[0042] (S.4) The porous filler is cleaned, decontaminated and dried using an acid having a concentration of 5 to 25% and an alkali having a concentration of 10 to 30%. The outer shell and porous balls after magnetization in step (S.3) are assembled and fixed with the porous filler after decontamination and drying to obtain a magnetic composite filler.

[0043] Preferably, the width of the sieve used in the sieving step (S.1) is 200-500 mesh, and after sieving, the sieve is dried at 50-90° C. for 5-48 hours;

[0044] In the step (S.3), the mixed filler is injection molded at 140-180° C., and then placed in a magnetizer of 8000-20000 GS for magnetization, so that the outer shell and the porous ball have a constant magnetic field of 20-100 GS;

[0045] The porous filler in the step (S.4) is successively cleaned with 5-25% acid and 10-30% alkali to remove impurities and dried.

[0046] The screen width used in the sieving in step (S.1) is 200-500 meshes, which is conducive to removing large impurities and maintaining uniform particle size. At the same time, the density difference of the particles is small, the mixing uniformity is higher, and the structure of the injection molded outer shell and the porous ball is more stable.

[0047] When the amount of magnetic powder added in step (S.2) is less than 5 parts, the iron oxide content in the magnetic powder is low, which will directly lead to poor magnetization effect after injection molding of the mixed filler in the subsequent step. The magnetic composite filler after magnetization has a certain weak magnetic field, and the degradation rate of waste gas by microorganisms attached to its surface will increase with the increase of magnetic field strength. The magnetic powder has the highest density in the entire magnetic composite filler component. When the amount of magnetic powder added exceeds 15 parts, a density difference will occur during the granulation process, which seriously affects the mixing uniformity. In addition, in the subsequent injection molding process, when the amount of magnetic powder added is too much, the dispersibility is poor and compression molding is difficult. Sedimentation is very easy to occur, which directly affects the normal molding of the injection molding machine and results in a high rate of defective injection molded parts.

[0048] In step (S.3), the temperature of the mixed filler injection molding is lower than 140°C or higher than 180°C, which will affect the rheological properties of the mixed filler at high temperature, affect the mixing uniformity, and further affect the quality of the injection molded parts. On the other hand, the outer shell and the porous ball have a constant weak magnetic field of 20 to 100GS, which can improve the activity of the degradation bacteria and effectively stimulate the growth and metabolism of microorganisms. A strong magnetic field exceeding 100GS will inhibit the activity of the degradation bacteria, resulting in a poor degradation effect and a reduced waste gas degradation rate.

[0049] As further preferred, the acid is generally an inorganic acid, which may be nitric acid, sulfuric acid, or hydrochloric acid, and the alkaline solution may be a sodium hydroxide solution, a potassium hydroxide solution, or a sodium carbonate solution.

[0050] In step (S.4), the porous filler is washed with acid and alkali successively, which can effectively remove impurities in the porous filler. At the same time, it is helpful to increase the roughness of the surface of the porous filler and further enhance the adhesion of microorganisms.

[0051] Therefore, the present invention has the following beneficial effects:

[0052] (1) The present invention effectively improves the internal porosity of the outer shell and the porous ball by fixing them together, and with multiple flow holes, the gas flow channels are increased, and the pressure loss in the system is significantly reduced;

[0053] (2) The present invention uses a uniquely designed biological filler to guide the gas to disperse evenly in the reactor, further extending its residence time and enhancing the degradation effect in the biochemical reaction;

[0054] (3) The present invention magnetizes the outer shell and the porous ball, and then fills the porous filler. This allows a large amount of high-density heteropolar magnetic fields to gather in the magnetic composite filler, increasing the contact area between the magnetic composite filler and the microorganisms attached to the surface of the porous filler. Under the action of the heteropolar magnetic field, more microorganisms are promoted to have a magnetic effect, further increasing the activity of enzymes in the microorganisms.

[0055] (4) The present invention has low production cost, is durable, and is highly efficient and energy-saving, which is conducive to promotion and application in production practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 It is a schematic diagram of the structure when the magnetic composite filler is not filled with porous filler;

[0057] Figure 2 is a schematic diagram of the structure of the half shell;

[0058] Figure 3 Schematic diagram of the structure of the porous ball;

[0059] Figure 4 It is a schematic diagram of the explosion of magnetic composite filler;

[0060] Figure 5 The figure is a process flow chart for preparing magnetic composite fillers;

[0061] Figure 6 This is the graph of chlorobenzene concentration changes in the shake flask experiment;

[0062] Figure 7 This is a graph showing the concentration changes of carbon dioxide generated in the shake flask experiment;

[0063] Figure 8 This is a graph showing the change in chloride ion concentration in the solution after the degradation of chlorobenzene waste gas;

[0064] Fig. 9 This is a graph showing the changes in dehydrogenase activity (DHA) of the water phase and microorganisms on the filler in a shake flask experiment;

[0065] Fig.10 The graphs of chlorobenzene concentration changes and cell dry weight under different magnetic fields in the shake flask experiment;

[0066] Fig.11 It is a schematic diagram of magnetic fields of the same level (different polarity);

[0067] Fig.12 Schematic diagram of the magnetic field after the porous ball is magnetized;

[0068] Fig.13 It is a schematic diagram of the magnetic field after the circulation sheet on the outer shell is magnetized;

[0069] Fig.14 This is a graph showing the changes in chlorobenzene concentration and chlorobenzene removal rate in the trickling tower.

[0070] In the figure: outer shell 1; cavity 2; flow hole 3; porous ball 4; porous filler 5; half shell 6; flow sheet 7; connecting rod 8. DETAILED DESCRIPTION

[0071] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0072] Example 1

[0073] The implementation method of magnetic composite filler is as follows:

[0074] like Figure 1-4 As shown, the magnetic composite filler includes an outer shell 1, and a cavity 2 is arranged inside the outer shell 1. The outer shell 1 is also provided with a flow hole 3 connected to the cavity 2. A porous ball 4 is arranged in the cavity 2, and a porous filler 5 is filled between the porous ball 4 and the inner wall of the outer shell 1. In this embodiment, the actual position of the porous filler 5 is between the porous ball 4 and the inner wall of the outer shell 1. Figure 4 It is only an exploded schematic diagram of the hollow sphere of magnetic composite filler and does not represent the actual position of each structure.

[0075] The outer shell 1 comprises two upper and lower half shells 6 , which are interlocked with each other to form a complete spherical outer shell 1 .

[0076] As another embodiment, the outer shell 1 may be a polyhedral sphere, or a hollow sphere, or a solid sphere structure, so that the outer shell 1 has a large surface area.

[0077] The upper and lower half shells 6 are interlocked to form a complete spherical outer shell 1, so that the gas in the system is blocked by the spherical surface when passing through the outer shell 1. This causes the gas flow to bend and tilt to a certain extent, thereby reducing the intake rate of the exhaust gas. At the same time, the gas flow path becomes longer, which prolongs the gas residence time in the system. This is conducive to promoting more complete contact between microorganisms and exhaust gas, and further improving the degradation performance of microorganisms on exhaust gas.

[0078] The outer shell 1 is provided with radially staggered flow sheets 7, and flow holes 3 connected to the cavity 2 are formed between adjacent flow sheets 7. The provision of multiple flow sheets 7 effectively increases the specific surface area of ​​the magnetic composite filler, which is conducive to the growth of microorganisms. The design of the flow holes 3 is conducive to uniformly dispersing the direction of the gas in the system and prolonging its residence time. The resistance encountered by the gas during the circulation process is reduced, and the pressure loss in the system is also greatly reduced.

[0079] Two connecting rods 8 for fixing to the outer shell 1 are symmetrically arranged on the outer surface of the porous ball 4 , so that the porous ball 4 can be suspended inside the cavity 2 through the connecting rods 8 .

[0080] As another embodiment, the porous ball 4 has a hollow structure inside, and the porous ball 4 is formed by two left and right porous hemispheres interlocked with each other, with a certain gap between the left and right porous hemispheres.

[0081] The porous ball 4 is suspended inside the cavity 2 by the connecting rod 8, and its internal porosity exceeds 90%, which can effectively avoid the clogging of the filler. At the same time, during the degradation process, the porous filler 5 is fixedly filled between the porous ball 4 and the inner wall of the outer shell 1, and less than 50% of the space is occupied by microorganisms. The presence of the porous ball 4 with a hollow structure inside further promotes that the pressure loss in the system is always small.

[0082] The pore size of the porous filler 5 is 0.5-2 mm, and the porosity is greater than 90%.

[0083] As another embodiment, the porous filler 5 is a combination of one or more of burr balls, polyurethane foam, and polyurethane sponge.

[0084] The porosity of the porous filler 5 is greater than 90%, which is conducive to enhancing the adhesion of microorganisms on the surface of the porous filler 5. At the same time, the pore size of the porous filler 5 is selected to be 0.5 to 2 mm, which plays a role in drainage and dispersion of the gas in the system. When the pore size is less than 0.5 mm, the porous filler 5 is approximately a solid structure. It is difficult for the gas to pass through when it flows in, and the resistance encountered is too large, and the corresponding pressure drop will increase. When the pore size is greater than 2 mm, the gas passes directly when it flows in. Although it is not subject to resistance, there is no drainage and dispersion effect. It indirectly shortens the residence time of the gas in the system, further affecting the waste gas degradation rate. In addition, the porous filler 5 is fixedly filled between the porous ball 4 and the inner wall of the outer shell 1, which is conducive to the renewal and shedding of the biofilm on the surface of the porous filler 5.

[0085] Example 2

[0086] A method for preparing a magnetic composite filler comprises the following steps:

[0087] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0088] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0089] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0090] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0091] Example 3

[0092] A method for preparing a magnetic composite filler comprises the following steps:

[0093] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 1 part of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0094] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0095] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0096] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0097] Example 4

[0098] A method for preparing a magnetic composite filler comprises the following steps:

[0099] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 3 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0100] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0101] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0102] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0103] Example 5

[0104] A method for preparing a magnetic composite filler comprises the following steps:

[0105] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0106] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 5 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0107] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0108] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0109] Example 6

[0110] A method for preparing a magnetic composite filler comprises the following steps:

[0111] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0112] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 15 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0113] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0114] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0115] Example 7

[0116] A method for preparing a magnetic composite filler comprises the following steps:

[0117] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0118] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 0.5 parts of white mineral oil and 1.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0119] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0120] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0121] Example 8

[0122] A method for preparing a magnetic composite filler comprises the following steps:

[0123] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0124] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 4 parts of white mineral oil and 3 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0125] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0126] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0127] Example 9

[0128] A method for preparing a magnetic composite filler comprises the following steps:

[0129] (S.1) 60 parts of polypropylene, 2 parts of activated carbon, 0.5 parts of silane coupling agent KH-570, 2.5 parts of starch, 1.5 parts of diatomaceous earth, 1 part of hydroxyapatite, and 1 part of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0130] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0131] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0132] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0133] Example 10

[0134] A method for preparing a magnetic composite filler comprises the following steps:

[0135] (S.1) 90 parts of polypropylene, 5 parts of activated carbon, 3 parts of silane coupling agent KH-570, 2.5 parts of starch, 4 parts of diatomaceous earth, 5 parts of hydroxyapatite, and 5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0136] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0137] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0138] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0139] Comparative Example 1

[0140] A method for preparing a magnetic composite filler comprises the following steps:

[0141] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0142] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Stir evenly and granulate to obtain a mixed filler;

[0143] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0144] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0145] Comparative Example 2

[0146] A method for preparing a magnetic composite filler comprises the following steps:

[0147] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0148] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 2 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0149] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0150] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0151] Comparative Example 3

[0152] A method for preparing a magnetic composite filler comprises the following steps:

[0153] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0154] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 20 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0155] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0156] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0157] Comparative Example 4

[0158] A method for preparing a magnetic composite filler comprises the following steps:

[0159] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0160] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0161] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0162] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0163] Comparative Example 5

[0164] A method for preparing a magnetic composite filler comprises the following steps:

[0165] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 0.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0166] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0167] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0168] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0169] Comparative Example 6

[0170] A method for preparing a magnetic composite filler comprises the following steps:

[0171] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0172] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0173] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0174] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0175] Comparative Example 7

[0176] A method for preparing a magnetic composite filler comprises the following steps:

[0177] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0178] (S.2) adding 10 parts of magnetic powder to the solid mixed raw material in step (S.1), stirring evenly and granulating to obtain a mixed filler; (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and the porous balls have a constant magnetic field of 20GS;

[0179] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0180] Comparative Example 8

[0181] A method for preparing a magnetic composite filler comprises the following steps:

[0182] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0183] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 6 parts of white mineral oil and 5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0184] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, injection molding at 140° C. to obtain the outer shell and porous balls, and then placing them into a 10000GS magnetizer for magnetization, so that the outer shell and porous balls have a constant magnetic field of 20GS;

[0185] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively. Then, the outer shell and porous balls magnetized in step (S.3) are assembled and fixed with the porous filler after impurities are removed and dried to obtain a magnetic composite filler.

[0186] Comparative Example 9

[0187] A method for preparing a magnetic composite filler comprises the following steps:

[0188] (S.1) 74 parts of polypropylene, 4 parts of activated carbon, 1 part of silane coupling agent KH-570, 2.5 parts of starch, 2 parts of diatomaceous earth, 3.5 parts of hydroxyapatite, and 1.5 parts of polyvinyl alcohol are mixed and crushed, sieved through a 200-300 mesh sieve and classified, and then heated and dried at 50° C. for 10 hours, and naturally cooled to room temperature to obtain a solid mixed raw material;

[0189] (S.2) The solid mixed raw material in step (S.1) is thoroughly mixed with 1 part of white mineral oil and 0.5 parts of vegetable oil until droplets adhere to the surface of the solid mixed raw material but do not fall off. Then 10 parts of magnetic powder are added, stirred evenly and granulated to obtain a mixed filler;

[0190] (S.3) adding the mixed filler in step (S.2) into an injection molding machine, and performing injection molding at 140° C. to obtain the outer shell and the porous ball;

[0191] (S.4) The porous filler is cleaned and dried by using 5% nitric acid and 10% sodium hydroxide respectively, and then the outer shell and porous balls in step (S.3) are assembled and fixed with the porous filler after cleaning and drying to obtain a composite filler.

[0192]

Performance testing and analysis

[0193]

Experiment 1

[0194] A magnetic composite filler was obtained according to the preparation methods of Examples 2 to 10 and Comparative Examples 1 to 8, and a composite filler was obtained according to the preparation method of Comparative Example 9. A 310 mL sealed bottle was used as the biological reaction system, and blank, composite filler, and magnetic composite filler were added to three sealed bottles in sequence, thereby forming three experimental groups, namely: blank group, modified group, and modified magnetized group. A certain amount of inorganic salt culture medium and 1 mL of XCW-1 bacterial solution activated to the logarithmic growth phase were added to the three experimental groups at the same time (the strain selected in this experiment was a chlorobenzene-efficient degrading bacterium, Relstonia jolanecearum XCW-1, obtained by screening from the activated sludge of a chemical plant in Zhejiang Province), so that the total volume of the liquid phase was 100 mL, and then 9 μL of a concentration of 100 mg·L -1 Chlorobenzene (Shanghai McLean Biotechnology, available on the market) was added. Then the sealed bottles were placed in a 30°C, 160 r / min -1 The culture was shaken in a shaker and 0.8 mL of the gas in the bottle was taken every 4 to 5 h. Each group of experiments was repeated three times.

[0195] The concentration of chlorobenzene in the gas phase was quantitatively analyzed using a gas chromatograph (Agilent 6890, USA). The chromatographic column was an HP-Innowax capillary column (30m×0.32mm×0.5μm) corresponding to the FID detector, the vaporization chamber and detector temperatures were 200℃ and 180℃, respectively, and the column temperature was 100℃. Carrier gas: nitrogen; column flow rate: 1mL·min -1 ; Split ratio: 30:1; Injection volume: 800 μL. The concentration of the corresponding substrate chlorobenzene in each experimental group was determined according to the calibration curve method. The concentration of chlorobenzene in this test (mg·m -3 ) and the curve of the peak area determination is Y = 1.8776X-573.39, R 2 =0.9981.

[0196] The concentration of chlorobenzene in the shake flask experiment changes as follows Figure 6 shown.

[0197] from Figure 6The data analysis shows that the modified magnetized group has completely degraded chlorobenzene within 18 hours, while the modified group and the blank group need to delay 1 to 2 hours to achieve the same effect, which also shows that the microbial degradation rate of the modified magnetized group is higher than that of the other two experimental groups. Degradation bacteria are attached to the surface of the magnetic composite filler in the modified magnetized group, and the degrading bacteria contain a small amount of paramagnetic metal elements. Under the action of the static magnetic field, these metal elements are rearranged, thereby inducing the activity and synthesis of the enzymes in the degrading bacteria; this also further promotes the biofilm growth and metabolism of the degrading bacteria on the surface of the magnetic composite filler, which accelerates its degradation rate.

[0198]

Experiment 2

[0199] A magnetic composite filler is obtained according to the preparation methods of Examples 2 to 10 and Comparative Examples 1 to 8, and a composite filler is obtained according to the preparation method of Comparative Example 9. A 310 mL sealed bottle is used as the biological reaction system, and blank, composite filler, and magnetic composite filler are added to three sealed bottles in sequence; thereby three experimental groups are formed, namely: blank group, modified group, and modified magnetized group. A certain amount of inorganic salt culture medium and 1 mL of XCW-1 bacterial solution activated to the logarithmic growth phase are added to the three experimental groups at the same time (the strain selected in this experiment is a chlorobenzene-efficient degrading bacterium obtained by screening from the activated sludge of a chemical plant in Zhejiang Province—Relstonia jolanecearum XCW-1), so that the total volume of the liquid phase is 100 mL. Then add 9 μL of a concentration of 100 mg·L -1 Chlorobenzene (Shanghai McLean Biotechnology, available on the market); then place the sealed bottle in a chamber at a temperature of 30°C and a rotation speed of 160 r / min -1 The culture was shaken in a shaker and 0.8 mL of the gas in the bottle was taken every 4 to 5 hours. Each group of experiments was repeated three times and the concentration of generated carbon dioxide was measured by gas chromatograph.

[0200] A gas chromatograph (Agilent 6890, USA) was used to quantitatively analyze the CO2 concentration in the gas phase. The chromatographic column was a HP-Plot-Q capillary column (30m×0.32mm×20μm) corresponding to the TCD detector. The injection port and detector temperatures were 90℃ and 180℃, respectively, and the column temperature was 40℃. Carrier gas: N2; Total flow rate: 107mL·min -1 ; Split ratio: 50:1; Gas injection volume: 800 μL. The concentration of generated carbon dioxide was measured by gas chromatograph according to the calibration curve method. The CO2 concentration (mg·L -1 ) and the curve of the peak area determination is Y = 0.3363X + 0.3397, R 2 =0.9996.

[0201] The concentration of carbon dioxide generated in the shake flask experiment changes as follows Figure 7 shown.

[0202] from Figure 7 The data analysis shows that as the reaction time increases, the concentration of carbon dioxide generated gradually increases. After 15 hours of reaction, the concentration of carbon dioxide generated by the modified magnetized group is significantly higher than that of the other two experimental groups, and the rate of carbon dioxide generation is faster. When the degradation reaction lasts for 24 hours, the concentration of carbon dioxide generated in this experiment reaches a peak value, corresponding to 46 mg·L -1 This also shows that the modified magnetized group has a better degradation effect on chlorobenzene waste gas. Chlorobenzene waste gas diffuses from the gas phase to the liquid phase surface, and then diffuses from the liquid phase surface to the interface between the liquid phase and the biofilm, where it is degraded into carbon dioxide and water by microorganisms. In addition, chlorobenzene waste gas is used by the microbial cells themselves, and carbon dioxide is discharged through diffusion; therefore, the concentration of outlet carbon dioxide represents the intensity of the carbon source of microbial metabolism. The higher the outlet carbon dioxide concentration, the more chlorobenzene waste gas is degraded by microorganisms.

[0203]

Test 3

[0204] After the shake flask experiment in Experiment 1 or Experiment 2 was completed, 1 mL of the solution was taken and detected by ICS-2000 ion chromatography. The separation column was AS19 (4.0×250 mm), the conductivity detector was 35°C, and the eluent was KOH (concentration gradient 10 to 40 mmol·L -1 ), flow rate 1.00 mL min -1 The injection volume is 25 μL. Before injection, the sample is filtered through a 0.45 μm filter membrane and a sodium cation exchange column. The chloride ion concentration in the solution is measured according to the calibration curve method. The chloride ion concentration in this test (mg·L -1 ) and the curve of the peak area determination is Y = 3.3197X + 0.0344, R 2 =0.999.

[0205] The change of chloride ion concentration in the solution after degrading chlorobenzene waste gas is as follows Figure 8 shown.

[0206] from Figure 8 The data analysis shows that after the modified magnetized group degraded chlorobenzene waste gas, the chloride ion concentration in the solution was always higher than that in other experimental groups. This phenomenon also corresponds to the performance difference in the reaction system, indicating that the modified magnetized group has better performance in product metabolism. The degradation rate of the substrate in the modified magnetized group was fast and the reaction was complete, while the other experimental groups did not react thoroughly during the degradation process, resulting in a part of chloride ions in the intermediate product, which led to a lower chloride ion concentration in the solution.

[0207] [Experiment 4] Determination of dehydrogenase activity (DHA) of the aqueous phase and microorganisms on the filler in the shake flask experiment After the shake flask experiment in Experiment 1 or Experiment 2 is completed, the aqueous phase in the shake flask corresponding to the three experimental groups is used as the test solution. Add 0.3 mL of the test solution, 1.5 mL of Tris-HCl buffer (pH = 7.5), and 1 mL of 0.2% INT (iodonitrotetrazolium violet) solution to a 10 mL centrifuge tube in sequence (add 1 mL of pure water to the blank tube). Quickly place the prepared sample in a 37°C water bath for shaking culture for 30 minutes, add 1 mL of 37% formaldehyde to terminate the enzyme reaction; 5000 r·min -1 Centrifuge for 5 min, discard the supernatant, add 5 mL of methanol, mix and stir evenly, and continue to extract at 37 ° C in the dark for 10 min, 4000 r / min -1 Centrifuge for 5 min, take the supernatant and measure the absorbance at 485 nm. The dehydrogenase activity in the solution is measured according to the calibration curve method. -1 ·h -1 ) and the absorbance curve is Y = 0.8601X + 0.018, R 2 =0.9969.

[0208] The changes of dehydrogenase activity (DHA) of microorganisms in the solution and on the filler after degrading chlorobenzene waste gas are as follows Fig. 9 shown.

[0209] from Fig. 9 From the data analysis, it can be seen that after the modified magnetized group degraded chlorobenzene waste gas, the dehydrogenase activity on the filler was always higher than that of other experimental groups. Because the surface of the filler is uneven, it provides a lot of growth space for microorganisms. In addition, microorganisms can attach to the surface of the filler and grow normally. The nutrients inside the filler can also promote the growth of microorganisms. Usually, microorganisms are negatively charged, and magnetized fillers are easily attached to them by microorganisms. This further shows that the modified magnetized group has a faster degradation rate and better performance in corresponding metabolism.

[0210] The dehydrogenase activity of all groups in the water phase is always weaker than that on the filler. This may be because the microorganisms in the water are easily dispersed by the water flow, have no carrier to attach to, and have insufficient resistance to environmental impact, which also causes their overall dehydrogenase activity to be low.

[0211]

Experiment 5

[0212] A 310mL sealed bottle was used as the biological reaction system. Magnets were added to both sides of two sealed bottles (the magnetic field strength in the middle was 20mT) to form stable homopolar magnetic fields and heteropolar magnetic fields respectively. At the same time, a blank was added to the third sealed bottle to make it without a magnetic field, thus forming three experimental groups. The three experimental groups were: homopolar magnetic field group, heteropolar magnetic field group, and blank group. A certain amount of inorganic salt culture medium and 1mL of XCW-1 bacterial solution activated to the logarithmic growth phase were added to the three experimental groups at the same time (the strain selected in this experiment was a highly efficient chlorobenzene degrading bacterium, Relstoniajolanacearum XCW-1, obtained by screening from the activated sludge of a chemical plant in Zhejiang Province), so that the total volume of the liquid phase was 50mL. Then 4.5μL of 100mg·L -1 Chlorobenzene (Shanghai McLean Biotechnology, available on the market); then the sealed bottles were placed in a 30°C, 160 r / min -1 The culture was shaken in a shaker and 0.8 mL of the gas in the bottle was taken every 4 to 5 h. Each group of experiments was repeated three times.

[0213] The absorbance (OD) of the cells was measured at a wavelength of 600 nm using a UV / visible spectrophotometer (Hitachi High Technologies, Japan). 600 ), and according to the absorbance of the bacteria (OD 600 ) and biomass dry weight to calculate the dry weight of bacterial cells. In this test, the dry weight of bacterial cells (mg·L -1 ) is Y = 910X-2.8, R 2 =0.974.

[0214] Changes in chlorobenzene concentration and cell dry weight under different magnetic fields in shake flask experiments Fig.10 shown.

[0215] from Fig.10The data analysis shows that the heteropolar magnetic field group has completely degraded chlorobenzene within 16 hours, while the homopolar magnetic field group and the blank group need to delay 1 to 3 hours to achieve the same effect. As the reaction time increases, the dry weight of the degrading bacteria in the heteropolar magnetic field group increases more, which shows that the degradation effect and microbial content of the heteropolar magnetic field group are higher than those of the other two experimental groups. The reason may be that microorganisms in nature are generally negatively charged; while the magnetic filler of the present invention is positively charged, and the heteropolar magnetic fields will show attraction in this experiment. Under the magnetic force of the magnetic filler, the microorganisms in the system can move continuously along the tangent direction of each point on the magnetic flux line, increasing the dispersion of the microorganisms. In addition, some microbial aggregate particles with higher density are prone to sedimentation due to gravity. The magnetic force of the heteropolar magnetic field can effectively prolong the suspension time of microorganisms in the solution and enhance their activity. Since the homopolar magnetic field will show repulsion, although the microorganisms can also move along the tangent direction of each point on the magnetic flux line, their movement will be affected by the repulsion, the moving distance is limited, and the corresponding dispersion is also low. Since the microorganisms in the blank group are only affected by gravity, their activity is more restricted, which corresponds to the difference in microbial content in the system. In view of this, the present invention magnetizes the magnetic composite filler so that its corresponding magnetic field is synchronously adjusted to a heteropolar magnetic field.

[0216] In summary, the reference polar magnetic field is shown in the figure Fig.11 -B, the magnetic field of the same polarity is as shown Fig.11 -A and 11-C. For magnetic composite fillers, the magnetic field diagram of the porous ball after magnetization is as follows Fig.12 As shown, the magnetic field diagram of the flow sheet on the outer shell after magnetization is as follows Fig.13 Its application in a trickling filter is shown in Experiment 6.

[0217]

Experiment 6

[0218] The simulated waste gas enters from the bottom of the reactor and is discharged from the top of the reactor. The inlet concentration of chlorobenzene waste gas is maintained at 200 mg·m -3 The pH of the inorganic salt nutrient solution is controlled at 7.0, the temperature is 30°C, and the spraying volume of the nutrient solution is 5-8 L·h -1 The residence time is 60s. After 25 days of operation, the biofilm formation is completed when the biofilm formation is basically stable. After the biofilm formation is completed, the concentration of chlorobenzene waste gas increases to 350mg·m -3The experiment is divided into a modified group (i.e., inorganic salt culture medium, degradation bacteria seed liquid, composite filler and chlorobenzene) and a modified magnetized group (i.e., inorganic salt culture medium, degradation bacteria seed liquid, magnetic composite filler and chlorobenzene). The composite filler obtained according to the preparation method of Comparative Example 9 is added to the reactor of the modified group, while the same amount of magnetic composite filler obtained according to the preparation methods of Examples 2 to 10 and Comparative Examples 1 to 8 is added to the modified magnetized group. Both groups of reactors are operated in a stable state. The reactor is operated continuously, and 500 mL of nutrient solution is replaced every 3 days. The substrate concentration at the inlet and outlet and the parameters required for the experiment are measured every day.

[0219] The calculation method of removal efficiency (RE) and empty bed residence time (EBRT) is as follows:

[0220]

[0221]

[0222] Where Q is the intake air flow rate, m 3 ·h -1 ;

[0223] C in is the intake chlorobenzene concentration, mg·m -3 ;

[0224] C out is the outgassing chlorobenzene concentration, mg·m -3 ;

[0225] V is the actual working volume of the reactor, m 3 .

[0226] The changes of chlorobenzene concentration and chlorobenzene removal rate in the trickling filter are as follows: Fig.14 shown.

[0227] from Fig.14 The data analysis shows that the removal rate of chlorobenzene in the modified magnetized group can reach more than 70.1% after the 24th day of biofilm formation, and can continue to maintain this removal performance, while the removal rate of the modified group is only 58.7%. -3When the removal rate of the modified magnetized group was basically stable at about 68.8%, while the removal rate of the modified group was maintained at about 52.7%, which also shows that the chlorobenzene removal rate of the modified magnetized group is always higher than that of the modified group. Since the degradation bacteria contain a small amount of paramagnetic metal elements, these metal elements will be rearranged under the action of the static magnetic field, which enhances the activity of enzymes in the microorganisms and increases their reaction rate; this also further promotes the growth and metabolism of microorganisms, and ultimately accelerates their degradation rate. Since microorganisms in nature generally carry negative charges, they are more easily adsorbed on the surface of the substrate under the static magnetic field of the magnetic composite filler, which also increases the number of microorganisms on the surface of the magnetic composite filler, and the corresponding degradation performance of chlorobenzene waste gas is also improved.

[0228] In summary, the present invention effectively improves the internal porosity by fixing and assembling the outer shell and the porous ball; with multiple flow holes, the gas flow channels are increased, and the pressure loss in the system is significantly reduced. The gas is guided to be evenly dispersed in the reactor by designing a uniquely structured biological filler, which further prolongs its residence time and strengthens the degradation effect in the biochemical reaction. In addition, by magnetizing the outer shell and the porous ball and then filling the porous filler, a large amount of high-density heteropolar magnetic fields are gathered in the magnetic composite filler, and the contact area with the microorganisms attached to the surface of the porous filler is also greatly increased. Under the action of the heteropolar magnetic field, the unique structure of the filler promotes more microorganisms to have a magnetic effect, which further increases the enzyme activity in the microorganism. The present invention has a low production cost, is durable, and is energy-efficient, which is conducive to promotion and application in production practice.

[0229] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A magnetic composite filler, characterized in that: The invention comprises an outer shell (1), wherein a cavity (2) is arranged inside the outer shell (1), and a flow hole (3) connected to the cavity (2) is also arranged on the outer shell (1), and a porous ball (4) is arranged inside the cavity (2), and a porous filler (5) is filled between the porous ball (4) and the inner wall of the outer shell (1), and the porous ball (4) and the outer shell (1) are magnetic, and two connecting rods (8) for fixing the porous ball (4) to the outer shell (1) are symmetrically arranged on the outer surface of the porous ball (4), so that the porous ball (4) can be suspended inside the cavity (2) through the connecting rods (8). The outer shell (1) and the porous ball (4) comprise the following components, calculated by weight: 60-90 parts of plastic, 2-5 parts of activated carbon, 5-15 parts of magnetic powder, 0.5-4 parts of liquid dispersant, 0.5-3 parts of silane coupling agent, 1-3 parts of starch, 1.5-4 parts of diatomaceous earth, 1-5 parts of hydroxyapatite, and 1-5 parts of polyvinyl alcohol.

2. A magnetic composite filler according to claim 1, characterized in that: The outer shell (1) comprises two upper and lower half shells (6), and the half shells (6) are interlocked with each other to form a complete spherical outer shell (1).

3. A magnetic composite filler according to claim 1 or 2, characterized in that: The outer shell (1) is provided with radially staggered circulation sheets (7), and circulation holes (3) connected to the cavity (2) are formed between adjacent circulation sheets (7).

4. A magnetic composite filler according to claim 1, characterized in that: The porous filler (5) has a pore size of 0.5-2 mm and a porosity greater than 90%.

5. The magnetic composite filler according to claim 1, characterized in that: The liquid dispersant is white mineral oil, vegetable oil or a combination of the two.

6. The magnetic composite filler according to claim 1, characterized in that: The plastic is a combination of one or more of polyethylene, polypropylene, and acrylonitrile-butadiene-styrene copolymer.

7. A method for preparing a magnetic composite filler as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (S.1) crushing, sieving and classifying plastic, activated carbon, silane coupling agent, starch, diatomaceous earth, hydroxyapatite and polyvinyl alcohol, heating and drying, and naturally cooling to room temperature to obtain a solid mixed raw material; (S.2) fully mixing the solid mixed raw material and the liquid dispersant in step (S.1), adding magnetic powder, stirring evenly and granulating to obtain a mixed filler; (S.3) injection molding the mixed filler in step (S.2), and then magnetizing to obtain the outer shell (1) and the porous ball (4); (S.4) Assembling and fixing the outer shell (1) and the porous ball (4) obtained in step (S.3) with the porous filler (5) to obtain a hollow ball of magnetic composite filler.

8. The method for preparing a magnetic composite filler according to claim 7, characterized in that: The sieve used in the step (S.1) is 200-500 mesh, and after sieving, the sieve is dried at 50-90°C for 5-48 hours; In the step (S.3), the mixed filler is injection molded at 140-180°C, and then placed in a magnetizer of 8000-20000GS for magnetization, so that the outer shell (1) and the porous ball (4) are both provided with a constant magnetic field of 20-100GS; The porous filler (5) in the step (S.4) is successively cleaned with an acid having a concentration of 5 to 25% and an alkali having a concentration of 10 to 30% to remove impurities and dried.

Citation Information

Patent Citations

  • Filler and multi-faceted hollow sphere for liquid and gas treatment and preparation method of filler as well as liquid and gas treatment method

    CN103627086A

  • Large biofilm culturing amount MBBR suspended biofilm carrier and preparing method thereof

    CN107758847A